Mercury Analysis in Blood Clams (Anadara granosa) in EEA of The Bagek Kembar, West Lombok - Sania, Neza Okta; Sedijani, Prapti; Suyantri, Eni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Gold mining activities can cause environmental degradation and have negative impacts on human health. This study aimed to analyze mercury concentrations in blood cockles (Anadara granosa) in the Essential Ecosystem Area (EEA) of the Bagek Kembar Mangrove, Sekotong, West Lombok. Sampling was conducted using 10 x 10 meter quadrants, and the data were analyzed using a Cold Atomic Absorption Analyzer of Mercury (CAAAM). Based on the analysis results, mercury concentrations in the flesh of Anadara granosa were in the range of 0.0057 to 0.0394 mg/kg, with the highest average concentration recorded at the station closest to the tourist area (0.0357 mg/kg). Despite this, the mercury levels remain below the safety threshold established by National Agency of Drug and Food Control (BPOM) Regulation No. 9 of 2022, which is 1.0 mg/kg. Therefore, regular environmental monitoring and increased public awareness about the dangers of mercury use are strongly recommended tu support the long-term preservation of marine ecological system and safeguard the safety of seafood consumption. Future research is suggested to assess the safe daily intake limit of Anadara granosa for local communities based on the detected mercury levels, in order to evaluate potential health risks to consumers.